Bond strength of GFRP bars in ultra-high strength concrete using RILEM beam tests. (March 2017) - Hossain, K.M.A.; Ametrano, D.; Lachemi, M.
Abstract: This paper presents a study about the bond characteristics of glass fiber reinforced polymer (GFRP) bars in ultra-high strength concrete (UHSC). One hundred forty four beam specimens having variable parameters namely bar diameter, GFRP bar types (standard low modulus 'LM' and high modulus 'HM'), three UHSC strength/class and embedded length (3, 5 and 7 times bar diameter) were tested as per RILEM specifications. The influence of each of these parameters was analysed to understand interface bond between GFRP bars and UHSC. Bond stress-slip characteristics and failure modes of the pullout specimens as well as influence of variable parameters on bond strength are described. The performance of various Codes and other existing equations in predicting bond strength of both low/high modulus GFRP bars embedded in UHSC is described based on experimental results. The bond strength decreased with the increase of embedment length - maximum bond strength reductions of 31% and 37% were observed for HSC and UHSC, respectively. For both HSC/UHSCs, bond strength reduced with the increase of bar size with maximum bond strength reduction of 12% and 42% for LM and HM bars, respectively. Code based and other existing equations were found conservative in predicting bond strength. Highlights: Studied bond strength of sand coated GFRP bars in ultra-high strength concrete (UHSC). RILEM beam tests were used. Influences of GFRP bar diameter/types, UHSC strength and embedded length were studied. Performance of Code based & other existing equations in predicting bond stress is described.